Axial crushing of aluminum extrusions filled with PET foam and GFRP. An experimental investigation. (February 2016) - Costas, M.; Morin, D.; Langseth, M.; Romera, L.; Díaz, J.
Abstract: This research work investigated the axial crushing behavior of a circular aluminum extrusion in alloy AA6063-T5 internally reinforced with a glass–fiber structure and filled with polymeric foam. The components were experimentally tested under quasi-static and impact loading conditions supported by a material testing campaign. Energy absorption, crush force efficiency and specific energy absorption were experimentally measured in order to assess the performance of a design proposal. Besides, the interaction effects between the different materials have been analyzed in depth and compared to the results for aluminum foam filled extrusions available in the literature. The confinement effect of the foam on the glass fiber plates has been found to have a very remarkable contribution to the energy absorption levels of the component, whereas a negligible foam–extrusion interaction was observed due to the gaps in the initial geometry of the specimen. The investigated component showed an overall good performance: the absorbed energy increased by almost 100% compared to an empty extrusion, the specific energy absorption was reduced by approximately 15% and the crush force efficiency was increased from 0.41 to 0.83. Abstract : Highlights: This paper presents the experimental axial crushing of a new crash box design. A PET foam–GFRP structure was used to fill aluminum extrusions. Components were tested under quasi-static and impact conditions. The interaction effect between the filling materials was investigated and quantified.